2018
DOI: 10.23851/mjs.v29i2.182
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Benign and Malignant Primary Bone Tumors-A Histopathological Study of 119 Cases

Abstract: This is a prospective study done at Al wasity teaching hospital for reconstructive surgeries in Bagdad in a period from November 2014 to April 2017, using a Total of 119 samples of primary bone tumors which were diagnosed both histopathologically and radiologically. The main objectives of this study was to make a comparison between benign and malignant bone tumors. Immunohistochemical staining was done to confirm the diagnosis of primary malignant bone tumors and the proliferative index of them were carefull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…12 In present study we evaluate 68 cases of neoplastic lesions of bone, we observed that these lesions are more common in younger persons between 20 -40 years of age, as observed by other studies 13 and the male (60.3%) were found affected more than the females, this was also the observation of other researchers mentioned in the literature. 1,7,10,14 We detect majority of benign (63.2%) cases in our study, which was in consistent with the findings of other studies 10,13,15 some studies showed a very high (84%) frequency of benign tumors 16 , these differences may be due to differences in sample size and selection criteria. Among 43 benign tumors, we diagnose majority (25.6%) of cases as osteochondroma followed by 21 % cases of Benign Giant Cell Tumor.…”
Section: Discussionsupporting
confidence: 91%
“…12 In present study we evaluate 68 cases of neoplastic lesions of bone, we observed that these lesions are more common in younger persons between 20 -40 years of age, as observed by other studies 13 and the male (60.3%) were found affected more than the females, this was also the observation of other researchers mentioned in the literature. 1,7,10,14 We detect majority of benign (63.2%) cases in our study, which was in consistent with the findings of other studies 10,13,15 some studies showed a very high (84%) frequency of benign tumors 16 , these differences may be due to differences in sample size and selection criteria. Among 43 benign tumors, we diagnose majority (25.6%) of cases as osteochondroma followed by 21 % cases of Benign Giant Cell Tumor.…”
Section: Discussionsupporting
confidence: 91%
“…Based on these findings, these cases in our study were re-diagnosed as high grade RMS. (23,24,25). It was evident that Desmin diffuse positive staining in four cases (8%) that could be due to the fact that Desmin is more specific for myogenic differentiation but it is less specific than Actin.…”
Section: Resultsmentioning
confidence: 98%